Analysis of Micro-Morphology, Thermal Conductivity, Thermal Diffusivity and Specific Heat Capacity of Coconut Fibre Reinforced Foamed Concrete - Othuman Mydin, M.A.; Rozlan, N.A.; Md. Sani, N.; Ganesan, S. (EDP Sciences, 2014)
With the quest for green construction and affordable housing systems for both rural and urban populations in Malaysia, various proposals focusing on cutting down on conventional building material costs have been put forward. One vanguard suggestion has been the sourcing, development and use of alternative, non-conventional local construction materials including the prospect of using some agricultural wastes as construction materials. This research describes experimental studies on the use of coconut coir fibre as an enhancer of foamed concrete with a focus on 2 parameters which are morphology properties and thermal properties of different percentages of coconut fibre (0%, 0.2% and 0.4%). In this study the addition of coconut fibre significantly improved all the properties investigated. The results of the tests showed that the thermal properties of foamed concrete improved with an increase in the proportion of coconut fibre. Findings from this research will also be used to address the knowledge gap on the subject of foamed concrete and will provide an improved understanding and raised awareness of the potential for using waste materials for domestic construction.